Becoming adults together: how having a disabled sibling impacts on young people’s transition to adulthood - Todd, Georgia (2019)
This thesis explores how having a sibling with learning disabilities or autism might impact on young people’s thoughts, experiences and aspirations relating to their transition to adulthood. Previous research has highlighted that having a disabled sibling impacts on people’s lives in different ways throughout the life course. Most research has focused on children and adolescent’s experiences or the experiences of older adults. There have been some studies that explore the experiences of young adults who have a disabled sibling. However, these studies mainly focused on young people’s views of service provision and how having a disabled sibling impacts on their plans for the future. The experiences of young adults are underrepresented in research relating to siblings of disabled people. There is also little understanding of how having a disabled sibling impacts on young people’s transition to adulthood.